2018
DOI: 10.1128/aem.00136-18
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Inference of Recombination-Mediated Evolution in Xanthomonas euvesicatoria and X. perforans

Abstract: Recombination is a major driver of evolution in bacterial populations, because it can spread and combine independently evolved beneficial mutations. Recombinant lineages of bacterial pathogens of plants are typically associated with the colonization of novel hosts and the emergence of new diseases. Here we show that recombination between evolutionarily and phenotypically distinct plant-pathogenic lineages generated recombinant lineages with unique combinations of pathogenicity and virulence factors. and are tw… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(70 citation statements)
references
References 74 publications
13
57
0
Order By: Relevance
“…To examine patterns of homologous recombination between Xp , Xeu , and other closely related Xanthomonas spp., a second core genome alignment was constructed utilizing the strains sequenced in this study and respective genome assemblies available from GenBank ( n = 68). A maximum likelihood phylogeny generated from the resulting 3.98 Mb alignment was largely congruent to the population structure inferred by previous studies (18, 20) and showed Xp and Xeu branching from each other into two distinct phylogenetic groups, while other related Xanthomonas spp. displayed considerably longer branch lengths and clustered into a paraphyletic group of strains.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…To examine patterns of homologous recombination between Xp , Xeu , and other closely related Xanthomonas spp., a second core genome alignment was constructed utilizing the strains sequenced in this study and respective genome assemblies available from GenBank ( n = 68). A maximum likelihood phylogeny generated from the resulting 3.98 Mb alignment was largely congruent to the population structure inferred by previous studies (18, 20) and showed Xp and Xeu branching from each other into two distinct phylogenetic groups, while other related Xanthomonas spp. displayed considerably longer branch lengths and clustered into a paraphyletic group of strains.…”
Section: Resultssupporting
confidence: 80%
“…The strains that belong to this larger phylogenetic group were classified into several species including X. alfalfae , X. axonopodis , X. perforans and X. euvesicatoria and are associated with diseases of diverse monocot and dicotyledonous plant families (23). While the importance of homologous recombination in facilitating the emergence of novel X. perforans lineages has been established (18, 19), the extent of genetic exchange across the larger X. euvesicatoria species complex and specific functional pathways affected by homologous recombination remains to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…4a), but because each recombination event introduces approximately six substitutions, recombination introduced substitution over mutation is 2.82 (95% CI: 2.81-2.83) times higher within recombinant fragments. These values were similar to those found in Indian Xoo populations [53] or what has been reported for other Xanthomonas species [59,60].…”
Section: Xoo Populations Show Distinct Signatures Of Mutation and Recsupporting
confidence: 90%
“…nov.) associated with watercress production in Florida were defined. Sequencing genomes of diverse strains belonging to closely related species infecting tomato and/or pepper indicated the admixture of strains arising due to frequent genetic exchange among different strains of the closely related species (Barak, Koike and Gilbertson 2002;Jibrin et al 2018). These hybrid strains pose a challenge to the current taxonomic definitions of a species based on average nucleotide identity (ANI).…”
Section: Taxonomic Re-classifications With the Knowledge Of Sequencedmentioning
confidence: 99%
“…Recombination-mediated evolution of bacterial plant pathogens is important for the colonisation in novel hosts and new disease emergence. Jibrin et al (2018) compared two newly sequenced Nigerian Xanthomonas strains (N1 and N38) with 70 previously published X. perforans and X. euvesicatoria strains. Recombination was identified as the major driving force of evolution of X. perforans and X. euvesicatoria strains, with X. perforans showing more evidence for recombination than X. euvesicatoria (Jibrin et al 2018).…”
Section: Genome Dynamics/plasticity-studying Evolutionary Processes Smentioning
confidence: 99%